2020
DOI: 10.22541/au.160133554.41583084/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is it better to treat bypass graft or native coronary artery following early graft failure?

Abstract: Several studies have already shown that coronary angiography and PCI can be safely performed after CABG. It is of paramount importance that early graft failure is recognized in a timely manner and that an appropriate treatment is delivered immediately in order to reduce the extent of myocardial damage and improve clinical outcome. Therefore, urgent angiography allows both identification of the underlying cause of early graft failure and immediate treatment according to the findings. So far, recent evidence sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…4,52,54 Conservative treatment may be indicated if angiography has excluded any mechanical or other overtly treatable cause. 49,55 Conservative treatment should be considered in patients who have a patent graft in the setting of PMI or in cases where baseline myocardial viability is already known to be limited. 50 Mechanical circulatory support should only be used as an adjunct rather than as a primary treatment.…”
Section: Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,52,54 Conservative treatment may be indicated if angiography has excluded any mechanical or other overtly treatable cause. 49,55 Conservative treatment should be considered in patients who have a patent graft in the setting of PMI or in cases where baseline myocardial viability is already known to be limited. 50 Mechanical circulatory support should only be used as an adjunct rather than as a primary treatment.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Intra-aortic balloon pump or peripheral extracorporeal membrane oxygenation can be considered in rescuing patients who develop significant hemodynamic instability before transfer to the OR or catheterization laboratory, or in the case of hemodynamic instability despite proven patent grafts and maximum inotropic support. 55 Irrespective of the strategy used, expeditious treatment is of paramount importance to minimize myocardial damage and to improve clinical outcomes. 8,13 Karhunen and colleagues 12 have reported that in comparison with patients with PMI who did not undergo repeat angiography, angiography was associated with a significant decrease in inhospital mortality (22% vs 46%, P ¼ .015) and a lower rate of emergency CABG reoperations.…”
Section: Treatment Optionsmentioning
confidence: 99%